Streaming Potential in Unconsolidated Samples Saturated with Monovalent Electrolytes - Duy Thanh, Luong (VNU Journal of Science: Mathematics - Physics; Vol 34 No 1, 2018)
The streaming potential coefficient of liquid-rock systems is theoretically a very complicated function depending on many parameters including temperature, fluid concentration, fluid pH, as well as rock parameters such as porosity, grain size, pore size, and formation factor etc. At a given porous media, the most influencing parameter is the fluid conductivity or electrolyte concentration. Therefore, it is useful to have an empirical relation between the streaming potential coefficient and electrolyte concentration. In this work, the measurements of the streaming potential for four unconsolidated samples (sandpacks) saturated with four monovalent electrolytes at six different electrolyte concentrations have been performed. From the measured streaming potential coefficient, the empirical expression between the streaming potential coefficient and electrolyte concentration is obtained. The obtained expression is in good agreement with those available in literature. Additionally, it is seen that the streaming potential coefficient depends on types of cation in electrolytes and on samples. The dependence of the streaming potential coefficient on types of cation is qualitatively explained by the difference in the binding constant for cation adsorption on the silica surfaces. The dependence of the streaming potential coefficient on samples is due to the variation of effective conductivity and the zeta potential between samples.